2020
DOI: 10.4103/jfmpc.jfmpc_294_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prevalence of depression among medical, dental, and engineering students in Patna using Beck's Depression Inventory II: A cross-sectional study

Abstract: Background: Depression, a multi-dimensional disorder adversely affects the interpersonal, social and occupational spheres of students’ life. It is the 11 th leading cause of global disease burden. Aims and Objectives: To assess the prevalence of depressive symptoms among various professional course students including medical, dental, and engineering students in Patna, Bihar. Materials and Methods: The present invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Undergraduate students, who are in transition from adolescence to youth, must successfully complete heavy courses and upgrade their resumes in order to find a suitable job in a competitive environment. Therefore, they are more prone to a variety of mental health problems such as depression (Lei et al 2016 ; Nezam et al 2020 ). Due to the lack of healthcare providers in the universities and their limited access to the diagnostic resources such as psychiatrists and psychologists, the problems cannot be detected, its severity may increase, and it may become a chronic depression (Farabaugh et al 2019 ; Hill et al 2015 ).…”
mentioning
confidence: 99%
“…Undergraduate students, who are in transition from adolescence to youth, must successfully complete heavy courses and upgrade their resumes in order to find a suitable job in a competitive environment. Therefore, they are more prone to a variety of mental health problems such as depression (Lei et al 2016 ; Nezam et al 2020 ). Due to the lack of healthcare providers in the universities and their limited access to the diagnostic resources such as psychiatrists and psychologists, the problems cannot be detected, its severity may increase, and it may become a chronic depression (Farabaugh et al 2019 ; Hill et al 2015 ).…”
mentioning
confidence: 99%
“…In two studies applying the BDI questionnaire, 10.9% of Brazilian intensive care nurses 48 (n=91) and 10.5% of Swedish men in a primary care unit 49 (n=223) had symptoms of depression. In another study among 2798 students using the same scale in India, 50 depressive symptoms were reported among 40.2%, 38.5% and 47.2% of engineering, dentistry and medical students, respectively. The reason for such studyto-study disagreement may be related to the type of questionnaire, study setting, nature of participants and study design applied.…”
Section: Discussionmentioning
confidence: 91%
“…Researchers revealed that sleeping between 5 and 5.9 hours increases the chance of occupational injury risk (odds ratio [OR] = 1.79), thereby compromising workers' safety 46 and health. 2 10 47 Yoon et al 47 showed that working <40 or >60 hours per week is associated with obesity in female Korean workers. The type of work was associated with obesity in nonmanual workers (OR = 1.20), and manual workers who work >60 hours had a higher likelihood of obesity (OR = 1.10).…”
Section: Discussionmentioning
confidence: 99%
“…9 Another study revealed that there was a 12% increased risk of obesity in female night work nurses compared with nurses working other shifts, and the possible explanations for this finding are sleep deprivation, inadequate eating habits, and lower light exposure. 10 European studies have shown that longer exposure to shift work was associated with obesity, dyslipidaemia, hyperglycaemia, and hypertension. 2,5 These bodily changes in workers can be explained by several factors, such as inadequate nutrition, sleep debt and/or sleep deprivation, as well as the result of desynchronization of the biological rhythm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation